Mendelian randomization studies of risk and protective factors for osteoporosis: a systematic review and meta-analysis - Ji, Wenhao; Pan, Bin; Chen, Xin; Lao, Zhaobai; Yang, Wanlei; Qian, Yu (Frontiers in Endocrinology, 2025)
BackgroundMendelian randomization is believed to attenuate the biases inherent in observational studies, yet a meta-analysis of Mendelian randomization studies in osteoporosis has not been conducted thus far. This study aims to evaluate the connection between potential causal factors and the risk of osteoporosis by synthesizing evidence from Mendelian randomization studies.MethodsThe databases PubMed, Web of Science, and Embase were systematically searched for Mendelian randomization studies investigating factors influencing osteoporosis up to May 2024. Meta-analyses were conducted to assess the associations between various potential pathogenic factors and osteoporosis using Mendelian Randomization studies. The quality of the study was evaluated according to the Strengthening the Reporting of Observational Studies in Epidemiology via Mendelian Randomization (STROBE-MR) guidelines.ResultsA total of 706 potentially relevant articles were screened, resulting in the inclusion of 53 studies in the systematic review, of which 30 were eligible for the meta-analysis. The combined findings from these 30 studies revealed that rheumatoid arthritis, inflammatory bowel disease, sex hormone binding globulin, depression, non-alcoholic fatty liver disease, primary biliary cholangitis and asthma are associated with increased risk of osteoporosis, while basal metabolic rate and gut microbiota (NB1n) serves as a protective factor. However, the association between obesity, type 2 diabetes mellitus, metformin, ulcerative colitis, leisure sedentary behaviors, systemic lupus erythematosus, serum iron and osteoporosis was found to be nonsignificant.ConclusionIn summary, our meta-analysis indicates that significant causal relationships with osteoporosis’s onset and progression have been established for rheumatoid arthritis, inflammatory bowel disease, primary biliary cholangitis, non-alcoholic fatty liver disease, depression, sex hormone binding globulin, basal metabolic rate, gut microbiota (NB1n), and asthma.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier PROSPERO CRD42024540504.